Home » The solution of the quadratic equation bx2 + cx + a = 0 is given…

The solution of the quadratic equation bx2 + cx + a = 0 is given…

The solution of the quadratic equation bx2 + cx + a = 0 is given by

  • A.
    x = b (pm) (frac{sqrt{b^2 – 4ac}}{2a})
  • B.
    x = c (pm) (frac{sqrt{b^2 – 4ab}}{2b})
  • C.
    x = -c (pm) (frac{sqrt{c^2 – 4ab}}{2b})
  • D.
    x = -b (pm) (frac{sqrt{b^2 – 4ac}}{2b})
Correct Answer: Option C
Explanation

bx2 + cx + a = 0
a = b; b = c; c = a
x = -b (pm) (frac{sqrt{b^2 – 4ac}}{2a})
x = -c (pm) (frac{sqrt{c^2 – 4ab}}{2b})